The role of interventional radiology in trauma patient care - Carnevale, Francisco Cesar; Moreira, Airton Mota (Revista de Medicina, 2011)
Trauma is a leading cause of death worldwide and a leading cause of disability. Trauma is a serious public health problem with significant social and economic costs. While advances in trauma care and trauma care systems have improved patient outcomes, research shows that Interventional Radiology (IR) can advance trauma care for stable, multiple trauma patients including those with vascular and solid organs lesions. Although requiring training, special machines and materials, IR may provide better results. Intra-abdominal injury should be suspected in instable pelvic / thoracic trauma cases. Bruising, petechiae or ecchymosis should be correlated to the vascular topography and organs. The peritoneal lavage, computed tomography, magnetic resonance and FAST (Focused Assesment with Sonography) may be necessary. Angiogram should not be indicated for acute abdominal trauma diagnosis because it can’t exclude associated lesions, but in the peripheral vascular area may be useful for planning. Despite surgery for severe cases, non-surgical treatment may determine a better outcome in many cases. The indication for embolization is based on the hemodynamic status and presence of active bleeding. Vascular and intra abdominal organ lesions may be treated by stenting, especially in cases of intimal and transmural vascular lesions or by embolization in bleeding cases. Liver injury can be conducted conservatively, surgically or by percutaneous embolization. The splenic and renal embolization should also be considered for selected patients. Small vascular extremity lesions, asymptomatic and non-occlusive, can be treated conservatively. In the neck region, IR is a good alternative to carotid lesions with difficult surgical access, above the angle of the mandible or petrous region. In turn, the use of covered and bare stents in the thoracic and abdominal aorta expands the treatment options. Pelvic and limb injuries require bone stabilization for adequate control. Further evidence comparing these techniques to surgery, are still needed